1990
DOI: 10.1099/00221287-136-7-1393
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of protein synthesis in the cyanobacterium Synechocystis sp. PCC 6803 after a salt shock

Abstract: Salt-induced changes in protein synthesis were investigated in the cyanobacterium Synechcystis sp. PCC 6803. Immediately after a salt shock of 684 mM-NaC1, total protein synthesis was almost completely blocked. Then, parallel to the accumulation of the osmoprotective compound glucosylglycerol, protein synthesis recovered gradually but remained diminished. The activation of glucosylglycerol synthesis was not inhibited by chloramphenicol at concentrations which totally inhibited protein synthesis. The qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 20 publications
(16 reference statements)
1
24
0
Order By: Relevance
“…It was a lag phase (3 days Vazquez-Duhalt and Arredondo-Vega 1991). Hagemann et al (1990) showed that immediately after NaCl was added to the medium, total protein synthesis in Synechocystis sp. PCC 6803 was almost completely repressed; repression of the synthesis of some proteins in Anabaena sp.…”
Section: Discussionmentioning
confidence: 99%
“…It was a lag phase (3 days Vazquez-Duhalt and Arredondo-Vega 1991). Hagemann et al (1990) showed that immediately after NaCl was added to the medium, total protein synthesis in Synechocystis sp. PCC 6803 was almost completely repressed; repression of the synthesis of some proteins in Anabaena sp.…”
Section: Discussionmentioning
confidence: 99%
“…They include certain integrins (14,15), receptors for angiogenic growth factors (16), proteases (17)(18)(19), and membrane proteins of unknown functions (20,21). Pericytes of angiogenic vessels express a membrane proteoglycan known as NG2 or high molecular weight melanoma antigen (22,23), and the extracellular matrix of angiogenic vessels contains an alternatively spliced form of fibronectin (24).…”
mentioning
confidence: 99%
“…The latter anti-id mAb was derived from a mouse immunized with the HMW-MAA-specific idiotypic mAb 763.74 (13). This antigen system was selected for our studies, since anti-id mAb MK2-23 has been found to elicit HMW-MAAspecific antibodies in mice and rabbits (14,15), both of which express orthologs of human HMW-MAA constitutively (16,17). In addition, anti-id mAb MK2-23 was able to induce HMW-MAA-specific humoral responses in patients with melanoma (18,19).…”
mentioning
confidence: 99%